Proteomics and Organoid Culture Reveal the Underlying Pathogenesis of Hashimoto’s Thyroiditis - Xiao, Hui; Liang, Jianqing; Liu, Sunqiang; Zhang, Qiongyue; Xie, Famin; Kong, Xingyu; Guo, Shanshan; Wang, Ruwen; Fu, Rong; Ye, Zhiqi; Li, Yun; Zhang, Shuang; et al. (Frontiers in Immunology, 2021)
Hashimoto's thyroiditis (HT) is an autoimmune disease and its incidence continues to rise. Although scientists have studied this disease for many years and discovered the potential effects of various proteins in it, the specific pathogenesis is still not fully comprehended. To understand HT and translate this knowledge to clinical applications, we took the mass spectrometric analysis on thyroid tissue fine-needle puncture from HT patients and healthy people in an attempt to make a further understanding of the pathogenesis of HT. 44 proteins with differential expression were identified in HT patients, and these proteins play vital roles in cell adhesion, cell metabolism, and thyroxine synthesis. Combining patient clinical trial sample information, we further compared the transient changes of gene expression regulation in HT and Papillary Thyroid Carcinoma (PTC) samples. More importantly, we developed patient-derived HT and PTC organoids as a promising new preclinical model to verify these potential markers. Our data revealed a marked characteristic of HT organoid in upregulating chemokines that include CCL2 and CCL3, which play a key role in the pathogenesis of Hashimoto's thyroiditis. Overall, our research has enriched everyone's understanding of the pathogenesis of HT and provides a certain reference for the treatment of the disease.